2011
DOI: 10.2109/jcersj2.119.577
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of thermal hysteresis in epitaxial VO2 films by doping metal ions

Abstract: Thermal hysteresises of electrical resistance, accompanying with a structural phase transition, in epitaxial VO 2 films have been successfully reduced to 1°C or less by doping Ti or Nb ions. We considered that owing to the metal-ion-substitutive structural defects induced by doping metal ions into VO 2 films, the structural phase transition easily occurred without superheating or supercooling. In Nb-doped VO 2 films, the hysteresis disappeared at a lower doping level than Ti-doped VO 2 films. The maximum value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
(13 reference statements)
0
26
0
Order By: Relevance
“…Our DSC results showed that the T C slightly decreases in low Ti concentration level (within about 3% Ti concentration), while a small amount of W doping (within 3.4% W concentration) will result in a distinct Tc decreasing ( Figure S1 ). Previous literatures also showed that the ability to regulate the T C in the Ti x V 1-x O 2 system was smaller than the M x V 1-x O 2 (M = W 6+ , Mo 6+ or Nb 5+ ) systems 12 19 26 33 36 43 . Table 1 shows the radius of several dopant ions and the V 4+ ion.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our DSC results showed that the T C slightly decreases in low Ti concentration level (within about 3% Ti concentration), while a small amount of W doping (within 3.4% W concentration) will result in a distinct Tc decreasing ( Figure S1 ). Previous literatures also showed that the ability to regulate the T C in the Ti x V 1-x O 2 system was smaller than the M x V 1-x O 2 (M = W 6+ , Mo 6+ or Nb 5+ ) systems 12 19 26 33 36 43 . Table 1 shows the radius of several dopant ions and the V 4+ ion.…”
Section: Discussionmentioning
confidence: 92%
“…Although Ti doping did not regulate the transition temperature significantly, Ti doping can effectively modify the thermochromic properties of VO 2 , such as the decrease of hysteresis sloop width of phase transition, the improvement of the temperature coefficients of resistance, and the enhancement of visible transmittance (T vis , 380–780 nm) and solar transmittance (T sol , 240–2600 nm) 33 34 35 36 37 . Compared with Ti x V 1-x O 2 film, there are no lattice mismatch and thermal stress for Ti x V 1-x O 2 nanopowders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the application, the hysteresis intrinsic to VO 2 can either be beneficial (as in memory devices) or detrimental (for devices which require fast on/off switching). Fortunately, a variety of methods to modulate the hysteresis width have been studied, including engineering of the size and shape of grain boundaries [31] and stresses [32], as well as the introduction of various metallic dopants [33] [34]. The aforementioned approaches have also been used to tailor the transition temperature of VO 2 within the ~0° C to ~100° C range [31] [32] [33] [14], further expanding the application space.…”
Section: Bb I K T K T I K Tmentioning
confidence: 99%
“…Doping of VO 2 with metal ions has been employed as a means of suppressing its thermal hysteresis; 13,14 however, doping with metal ions also gives rise to a reduction in the TCR of VO 2 . We previously conducted a systematic study of the TCR and thermal hysteresis in VO 2 doped with Cr or with Nb, and we found that there is a correlation between the TCR and thermal hysteresis, which is independent of the doping element.…”
Section: Introductionmentioning
confidence: 99%